Determining factors in adopting the social media applications for the development of sme in jaffna district - Kajanthy, S.; Sathana, V. (University of Jaffna, 2017)
The purpose of this study is to identify the seminal factors in adopting the social media applications for the SMEs development in Jaffna District. The adoption of social media applications to promote and carryout business activities in SMES is somewhat new. The quantitative approach was deemed appropriate for this study. Convenient sampling technique has been pursued to collect the primary data. Questionnaires were issued and gathered data from conveniently selected two hundred (200) SMES. Exploratory Factor Analysis (EFA) was used to find out the determinant factors of SMEs in order to adopt social media applications. To further prove the reliability of the data, Kaiser- Meyer_Olkin (KMO) and Bartlett Test of Sphericity were applied in this research. This study reveals five factors namely organizational factors, management factors, external environmental factors, technological innovativeness and customer factors influence the adoption of social media applications by SMEs. This paper offers valuable ideas to help SMEs to adopt social media as well as understand its value. There are many researches on social media related to large organizations rather than SMEs. This research reveals that considerable implications for decision makers in SMEs will become more in sync to how social media technology can meaningfully add value to them and for customers who would be able to get the information on the desk itself via social media instead of going out to field and collect information. Social Media Marketing would be a concrete foundation and supports to the SMEs to start their online marketing and E-marketing.
Keywords: Social Media; SMEs; Management; Firm Innovativeness; Business Environment